The Effect of Academic Supervision and Teacher Professionalism on Student Learning Outcomes - Temazisokhi Hulu; Tita Rosita; Arif Rahman; Syahril (South Sulawesi Education Development (SSED), 2024)
This study aims to analyze the influence of the academic and professional supervision of teachers on student learning outcomes. The study population amounted to 53 teachers, research sampling using saturated sampling techniques where the population was used as a research sample. The type of data or information used is primary data with data collection techniques through questionnaires. Data analysis techniques were carried out using descriptive and inferential analysis with multiple regression analysis methods using SPSS 25. The results of the analysis show that partial academic supervision has a positive effect on student learning outcomes, and teacher professionals have a positive effect on student learning outcomes. In contrast, simultaneously, academic supervision and teacher professionalism significantly affect student learning outcomes, so the improvement of student learning outcomes in elementary schools is influenced by the implementation of academic supervision and Professionalism of teachers in carrying out learning. Keywords: Academic Supervision, Professional Teachers, Learning Outcomes, Learners